1992
DOI: 10.1016/0741-5214(92)90713-i
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury in experimental thoracic aortic occlusion: investigation of combined methods of protection

Abstract: The efficacy of combined methods of spinal cord protection during thoracoabdominal aortic reconstruction was evaluated because a recent clinical study failed to substantiate the value of cerebrospinal fluid drainage when used alone in the prevention of paraplegia. The effect of cerebrospinal fluid drainage and aortofemoral shunting were analyzed with regard to neurologic outcome and spinal cord blood flow in a model of thoracic aortic occlusion. In addition, we studied the use of motor-evoked potentials as com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 21 publications
0
19
0
2
Order By: Relevance
“…In any case, cerebrospinal uid drainage cannot be regarded as the only and most effective maneuver to improve spinal cord blood ow. Elmore et al (79) showed that after 60 min of thoracic aortic occlusion in a dog model, spinal cord blood ow was signi cantly increased by cerebrospinal uid drainage as compared with controls as shown also by Bower et al (76). However, spinal cord blood ow was more than doubled by using aortofemoral shunt as compared with cerebrospinal uid drainage alone.…”
Section: Cerebrospinal Uid Pressure Monitoring and Drainagementioning
confidence: 84%
See 3 more Smart Citations
“…In any case, cerebrospinal uid drainage cannot be regarded as the only and most effective maneuver to improve spinal cord blood ow. Elmore et al (79) showed that after 60 min of thoracic aortic occlusion in a dog model, spinal cord blood ow was signi cantly increased by cerebrospinal uid drainage as compared with controls as shown also by Bower et al (76). However, spinal cord blood ow was more than doubled by using aortofemoral shunt as compared with cerebrospinal uid drainage alone.…”
Section: Cerebrospinal Uid Pressure Monitoring and Drainagementioning
confidence: 84%
“…In fact, passive shunts seem to provide suboptimal blood ow and perfusion pressure (<40 mmHg), whereas atriofemoral or femoro-femoral bypasses can adjust the mean distal aortic pressures between 60 and 70 mmHg (98), values which are more likely to maintain a spinal cord perfusion pressure above 40 mmHg (43). Furthermore, a better control of the proximal aortic and pulmonary artery pressures can be achieved without pharmacologic intervention (79), with potential positive effect on intracranial and cerebrospinal uid pressure.…”
Section: Distal Aortic Perfusionmentioning
confidence: 93%
See 2 more Smart Citations
“…The centrifugal pump is used for left heart bypass, 3,28,39 and provides the best means of maintaining distal aortic perfusion. By using centrifugal pumps flow can be regulated, there is less damage to the blood components than with roller pumps, minimal heparinization is required, and a reservoir can be used in the setting of trauma or a ruptured aneurysm.…”
Section: Distal Perfusionmentioning
confidence: 99%